SHALLOW GAS OFF THE RHôNE PRODELTA, GULF OF LIONS - García-García A.; Orange D.; Lorenson T.; Radakovitch O.; Tesi T.; Miserocchi S.; Berné S.; Normand A.; Friend P.L.; Nittrouer C. (My University, 2006)
Sediment cores acquired in 2004 off the Rhône prodelta show consistent anomalous methane concentrations of up to 87,440 ppm. Methane compositional and isotopic data support a biogenic origin, although there are a few sites that show strongly depleted δ13C values (- 53‰ PDB) suggesting a mixed source for the gas (biogenic and thermogenic). Anomalous methane concentrations (samples with more than 90 ppm) are discussed and integrated with organic carbon data, sedimentary rates and ADCP profiles. Highest gas concentrations were found directly off the river mouth (20-40 m water depth) and where the IFREMER models point to the thickest accumulation (> 2 m) in response to the Rhône flood event. In areas unaffected by the high flux of organic matter and rapid/thick flood deposition, or in between flood events, the conditions for methanogenesis and gas accumulation have not been met; in these areas, the physical and biological reworking of the surficial sediment may effectively oxidize and mineralize organic matter and limit bacterial methanogenesis in the sub-surface. We propose that in the Rhône prodelta flood deposits deliver significant amounts of terrigenous organic matter that can be rapidly buried, effectively removing this organic matter from aerobic oxidation and biological uptake and leading to the potential for methanogenesis with burial. © 2006 Elsevier B.V. All rights reserved.
Keywords: BIOGENIC METHANE; FLOOD DEPOSITS; GULF OF LIONS; RHôNE PRODELTA; SHALLOW GAS